Effect of Probiotic and Organic Acids in an Attempt to Replace the Antibiotics in Diets of Broiler Chickens Challenged with Eimeria spp. - Barbieri, Adriano; Polycarpo, Gustavo do Valle; Cardoso, Robert Guaracy Aparecido; Silva, Kelry Mayara da; Dadalt, Julio Cezar; Madeira, Alda Maria Backx Noronha; de Sousa, Ricardo Luiz Moro; Albuquerque, Ricardo de; Cruz-Polycarpo , Valquiria Cacao (International Journal of Poultry Science, 2015)
The effect of probiotic (Bacillus amyloliquefaciens) and organic acids (lactic, acetic and butyric acid), isolated or combined, in an attempt to replace the antibiotics (avilamycin+sodium monensin) on intestinal anaerobic bacteria, allometric growth of digestive organs, intestinal morphometric and performance of broilers challenged by Eimeria (acervulina, maxima and tenella) were studied in a 1 to 21-d experiment. A total of 900 male Cobb chicks were distributed in a completely randomized design in a 2 x 2 + 1 factorial arrangement, presence or absence of probiotic and organic acids more a positive control with antibiotics, with six replicates. The probiotic promoted some changes on total anaerobic microorganisms throughout the small intestine in both periods (p<0.02), whereas the antibiotics decreased this counting only until 14 days (p<0.04). Antibiotics increased liver weight at 14 days (p<0.01) and reduced the relative weight of the pro-ventricle, gizzard and all segments of the small intestine at 21 days (p<0.01). At 14 days, the alternative additives reduced the villus height and crypt depth (p<0.05), whereas the probiotic increased the width of the villus base (p<0.01). Antibiotics reduced the crypt depth and width of the villi in the small intestine in both periods (p<0.05). Although some changes in the intestinal microbiota and morphology, the alternative additives, isolated or combined, did not change the birds’ performance (p>0.05), only the antibiotics provided better results on BW gain and feed: gain in 1 to 14 and 1 to 21 d-old (p<0.05) of broilers challenged with Eimeria spp.